Genealogy Of The Inheritance of Grebeg Sabrang Mask Dance in Sanggar Asmorobangun in The Context of Identity Preservation - Hafri Ahsani, Daniar; Hartono Hartono; Agus Cahyono (Universitas Negeri Semarang, 2024)
The motivation for this research is the gaps that frequently occur during the process of inheriting cultural arts, particularly among the younger generation, who are beginning to lose touch with traditional values in the face of modernization. From a genealogical standpoint, the objective of this research is to investigate the inheritance process of the Grebeg Sabrang Masked Dance in Sanggar Asmorobangun Kedungmonggo Malang Regency. With family and local community-based inheritance patterns, this dance has been passed down through generations since the era of Mbah Serun until the fifth generation. This research employs qualitative methodologies, including participatory observation, documentation, and in-depth interviews, as data collection techniques. The validity of the data was verified by conducting a triangulation of sources, methods, and theories. This studio was able to adapt to the demands of the times by innovating the duration and function of dance, both as a medium of education and tourism, in addition to ensuring the sustainability of the tradition, as demonstrated by the results. This preservation process entails strategies that are designed to preserve the traditional essence of the performance form, collaborate between generations, and adjust the performance form in accordance with local cultural values. This research's conclusion shows the significance of the genealogical approach in the preservation of traditional art as a local cultural identity and its relevance in the contemporary era.